Analysis of Distribution Model of Matric Suction of Land Subsidence Caused by Foundation Pit Dewatering - WANG, Donglin (Engineering Transactions, 2015)
By the soil matrix suction distribution under one-dimensional steady-state flow, soil permeability coefficient ks, infiltration intensity q and initial groundwater table factors that influence the matric suction of unsaturated soil were analyzed in this paper. Based on unsaturated soil mechanics theory, ground subsidence caused by dewatering was calculated for typical pits and the impact of non-saturated soil matrix suction value on ground subsidence was taken into consideration. The results has shown that under steady infiltration conditions (q/ks < 0), the deformation of subsidence in unsaturated zone was bigger than the initial suction with still water distribution (q/ks= 0), while under stable evaporation conditions (q/ks > 0), the deformation of subsidence in unsaturated zones was smaller than the initial suction with still water distribution. In addition, as the groundwater table was lower, the influence of distribution patterns of the initial matrix suction in unsaturated soil on deformation of ground subsidence was greater.